2009
DOI: 10.1073/pnas.0906761106
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte scaffolding protein p55/MPP1 functions as an essential regulator of neutrophil polarity

Abstract: As mediators of innate immunity, neutrophils respond to chemoattractants by adopting a highly polarized morphology. Efficient chemotaxis requires the formation of one prominent pseudopod at the cell front characterized by actin polymerization, while local inhibition suppresses the formation of rear and lateral protrusions. This asymmetric control of signaling pathways is required for directional migration along a chemotactic gradient. Here, we identify the MAGUK protein p55/MPP1 as a mediator of the frontness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…Although MPP6 was previously shown not to interact with 4.1R (44), we demonstrate that it interacts with 4.1G in myelinating Schwann cells. The existence of an MPP6-4.1G complex in mouse Schwann cells is analogous to the MPP1 (p55)-4.1R complex found in erythrocytes (22,29,33), CASK-4.1N interaction in neurons (3), and MPP6-4.1B interaction in epithelial cells (34). In the 4.1G Ϫ/Ϫ mouse sciatic nerves, the total amount of MPP6 was significantly reduced and the protein was detected in the cytoplasm near the Schwann cell nuclei, which is abnormal.…”
Section: Discussionmentioning
confidence: 81%
“…Although MPP6 was previously shown not to interact with 4.1R (44), we demonstrate that it interacts with 4.1G in myelinating Schwann cells. The existence of an MPP6-4.1G complex in mouse Schwann cells is analogous to the MPP1 (p55)-4.1R complex found in erythrocytes (22,29,33), CASK-4.1N interaction in neurons (3), and MPP6-4.1B interaction in epithelial cells (34). In the 4.1G Ϫ/Ϫ mouse sciatic nerves, the total amount of MPP6 was significantly reduced and the protein was detected in the cytoplasm near the Schwann cell nuclei, which is abnormal.…”
Section: Discussionmentioning
confidence: 81%
“…Using a MPP1 knockout (p55 -/-) mouse model, Quinn et al ( 2009 ) showed that, upon agonist-stimulation of neutrophils, MPP1 is rapidly recruited to the leading edge. Neutrophils of knockout mouse do not migrate efficiently in vitro and form multiple pseudopods upon chemotactic stimulation, in contrast to normal mouse neutrophils, which form a single pseudopod at the cell front required for effi cient chemotaxis.…”
Section: Mpp1mentioning
confidence: 99%
“…Previously, we generated MPP1 knockout mice showing phenotypes unrelated to erythrocyte stability including defects in neutrophil polarity and Akt signaling. 9 With further breeding of the MPP1 KO mouse colony on a C57BL/6 genetic background, we observed developmental abnormalities with increasing frequency. To date, no human case of genetic abnormality in the MPP1 family has been reported.…”
Section: Mpp1/p55 Gene Deletion In a Hemophilia A Patient With Ectrodmentioning
confidence: 92%
“…We compared the developmental defects seen in the patient ( Figure 1A-D) with our established MPP1 null mouse model. 9 Sequential backcrosses onto wild type (WT) C57BL/6 mice were performed for at least 10 generations. No discernible limb development abnormality analogous to the patient's condition was observed.…”
Section: Mpp1/p55 Gene Deletion In a Hemophilia A Patient With Ectrodmentioning
confidence: 99%